Functional Analysis of 3-Dehydroquinate Dehydratase/Shikimate Dehydrogenases Involved in Shikimate Pathway in Camellia sinensis - Huang, Keyi; Li, Ming; Liu, Yajun; Zhu, Mengqing; Zhao, Guifu; Zhou, Yihui; Zhang, Lingjie; Wu, Yingling; Dai, Xinlong; Xia, Tao; Gao, Liping (Frontiers in Plant Science, 2019)
Polyphenols play an important role in the astringent taste of tea [Camellia sinensis (L.)] infusions; catechins in phenolic compounds are beneficial to health. The biosynthesis of gallic acid (GA), a precursor for polyphenol synthesis, in tea plants remains unknown. It is well-known that 3-dehydroquinate dehydratase/shikimate dehydrogenase (DQD/SDH) is a key enzyme for catalyzing the conversion of 3-dehydroshikimate (3-DHS) to shikimate (SA); it also potentially participates in GA synthesis in a branch of the SA pathway. In this study, four CsDQD/SDH proteins were produced in Escherichia coli. Three CsDQD/SDHs had 3-DHS reduction and SA oxidation functions. Notably, three CsDQD/SDHs showed individual differences between the catalytic efficiency of 3-DHS reduction and SA oxidation; CsDQD/SDHa had higher catalytic efficiency for 3-DHS reduction than for SA oxidation, CsDQD/SDHd showed the opposite tendency, and CsDQD/SDHc had almost equal catalytic efficiency for 3-DHS reduction and SA oxidation. In vitro, GA was mainly generated from 3-DHS through nonenzymatic conversion. qRT-PCR analysis showed that CsDQD/SDHc and CsDQD/SDHd expression was correlated with GA and 1-O-galloyl-β-D-glucose accumulation in C. sinensis. These results revealed the CsDQD/SDHc and CsDQD/SDHd genes are involved in GA synthesis. Finally, site-directed mutagenesis exhibited the mutation of residues Ser-338 and NRT to GLY and DI/LD in the SDH unit is the reason for the low activity of CsDQD/SDHb for 3-DHS reduction and SA oxidation.